Relating between Fluency and Reading Comprehension in Students with Learning Difficulties - Orlandi Cunha, Vera Lúcia (2017)
The capacity to read and comprehending text is essential in our daily life and in the educational context. Considering this aspect the objective of this study was to compare fluency and reading comprehension of students from second to fifth grade of primary school with and without learning difficulties. The eighty students who participated were divided into eight groups: GI to GIV (students without learning difficulties); GV to GVIII (students with learning difficulties). Of the oral reading of a text were measured the time, accuracy, speed and reading comprehension. Statistically significant differences were observed on all these variables indicating inferior performance to the students with learning difficulties. It was found that difficulties in reading fluency interfered with reading comprehension.